THE NATIONAL POLICY OF IRAN TOWARD VIOLENCE AGAINST WOMEN / A POLÍTICA NACIONAL DO IRAN PARA A VIOLÊNCIA CONTRA AS MULHERES - Rahpaymaelizehee, Shahnaz; Fallahi, Bahare; Jafari Kojouri, Razieh (Espaço Jurídico Journal of Law [EJJL], 2015)
Abstract: Iran’s 20-year Economic, Social and Cultural Development Perspective started in 2005 and will continue to 2025. It has outlined developments in the field of society, economics, politics and culture for the next twenty years. Unfortunately, it is not an overreaching plan, particularly in the area of violence against women. Although the government has considered different strategies in this national plan to confront and reduce this problem, it is not enough and this problem is still prevalent, especially in the rural areas. The aim of this literature review is to analyze the policies of the long-term economic and socio-cultural perspective of Iran to determine whether the national plan could meet its objectives in the field of violence against women. The findings of this study shows a lack of information pertaining to women and girls, their legal rights as stated in the Constitution and, Civil Laws and, particularly, in Iran’s long term development plan, which lead to mental and physical vulnerability. The ignorance of women concerning their rights due to the neglect of the legislative, executive and judicial authorities, and related organizations, such as the Center for Women’s Participation and women’s NGOs, in educating the women about this vital issue. Keywords: Violence. Women. Policy. National Plan.